Selection of superior cacao trees at the cacao plantations in Bahia, Brazil - Pinto, Geraldo Carlos P.; Magalhães, Walter S.; Marques, Edson Silva; Rodrigues, Everaldo M. (Pesquisa Agropecuaria Brasileira, 2014)
In Brazil, the State of Bahia with over 450,000 hectares under cultivation produces about 96% of all Brazilian cocoa; however, the average annual seed production is very low, around 0.450 kg of dry beans per tree. In 1953 the Instituto de Pesquisas e Experimentação Agropecuárias do Leste, started its cocoa selection program in the cocoa plantations of southern Bahia. The objectives were to improve yields per tree and resistance to Phytophthora pod rot. Selection was based on the following criteria: 1. High pod numbers; 2. Desirable pod shape; 3. Health of trees and pods, especially those with a low incidence of Phytophthora pod rot. Individual tree and the harvest data were recorded for comparative analysis. The following criteria of superiority were preestablished: 1. Average annual production of dry cocoa beans ≥ 4.0 kg. 2. Average annual production ≥ 100 fruits. 3. Fruit index ≤ 40. 4. Average percentage of infected fruits ≤ 12 or less. Pod production and resistance Phytophthora pod rot has been recorded for at least seven years on 1235 cocoa trees. Records on many these trees have been maintained for as long as eleven years. From the 1235 trees one hundred ninety seven were selected for asexual propagation and inclusion in the collection of cocoa clones at the Experimental Station of Juçari. From the 190 clones 28 exceptional trees were chosen using an appropriate statistical process of data on selection pod numbers, seed production, fruit index, a percentage of fruit infected by Phytophthora pod rot, tree population density, intensity to shade and stem appearance. The special criteria developed to evaluate each index are discussed as well as the degree of transmissibility of desired characteristics to a descendent population obtained by rooted cuttings.